Analysis of Consumptive Behavior of Indonesian Society During the Pandemic of Corona Virus (Covid-19) - Maulidya Shafira (Pena Cendekia Insani, 2020)
At the beginning of 2020, people around the world were shocked bythe Corona Virus (Covid-19) pandemic which caused paniceverywhere. Hundreds of thousands of people were infected andthousands more died. In Indonesia, the government has given appealsto the public by enforcing rules for working from home, worshiping,doing activities and staying at home for the safety and health ofresidents due to the corona virus pandemic which has resulted inbehavioral changes. people now rely on digital technology tocontinue their social life and communicate after the government'spolicy regarding PSBB and physical distancing. Activities are limitedwhere shopping is done from home. Online purchases are becomingmore frequent. This opportunity is certainly used by online stores thatoffer various things to attract consumers, such as ease of shopping,promotions, discounts, purchase bonuses and so on.